Comparison of oral misoprostol and intramuscular oxytocinfor treating of primary post partum haemorrhage caused byuterine atony - H. Abid AlKareem, Israa (Tikrit Journal of Pharmaceutical Sciences, 2023)
To compare oral misoprostol with intramuscular oxytocin in the treatment of atonic uterus that cause primary post partum haemorrhage after vaginai home deliveries .A prospective study , 38 women were categories in fwo group; as follow: twenty-five women received intramuscular oxytocin and thirteen received oral misoprostol. Measurement of the blood loss after medication was recorded as a main outcome measure. The result showed that 72o/o of the patient received intramuscular oxytocin injection had blood loss less that 500 ml while 46% of the patients received oral misoprostol had blood loss less than 500m1. Intramuscular oxytocin injection is effective in treatment of primary post partum hemonhage caused by uterine atony